LL37-coated ZPF-2 compound, pharmaceutical composition and application
By loading the antimicrobial peptide LL37 onto the metal organic framework material ZFP-2, forming the LL37@ZPF-2 complex and combining it with the poloxamer 407 gel solution, the problem of decreased antimicrobial peptide activity and inconvenient administration of traditional dosage forms in the wound environment is solved, and more efficient wound healing and more convenient administration methods are achieved.
Patent Information
- Application Number
- CN202411893664.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-15
AI Technical Summary
The activity and efficacy of existing wound healing drugs in alkaline wound environments have decreased, and the administration of traditional dosage forms is inconvenient, which affects the patient's tolerance and medication convenience.
A LL37@ZPF-2 complex was developed to form a composite by loading the antimicrobial peptide LL37 onto the metal organic frame material ZFP-2, and combined with the poloxamer 407 gel solution, using a spray delivery route.
It improves antibacterial efficacy and wound healing effect, enhances biocompatibility and thermal stability, simplifies the preparation process, and improves the convenience of administration and patient tolerance.
Smart Images

Figure CN119818648A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wound healing drugs, and in particular to a LL37@ZPF-2 complex, a pharmaceutical composition and applications. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] After surgery, burns, accidental injuries, skin diseases, microbial infections or metabolic dysfunction, the barrier function of normal skin tissue is destroyed, leading to the development of wounds. Wound healing is a basic process required to rebuild tissue integrity, repair skin barrier function and restore skin homeostasis. The typical wound healing process is characterized by four stages: inflammation, proliferation, hemostasis and remodeling. The failure of the damaged tissue recovery mechanism can lead to the formation of chronic non-healing wounds. For example, common diseases such as diabetes, venous or arterial diseases and microbial infections are prone to develop into chronic wounds, and some even develop into pathological non-healing ulcers. These ulcers are characterized by the inability of epithelial cells to migrate, proliferate and have defective barrier closure functions, such as chronic leg ulcers caused by venous insufficiency.
[0004] In addition to its antibacterial activity, human cathelicidin antimicrobial peptide LL37 (CAS: 145947-66-7) also has activities such as promoting wound repair and regeneration. Studies have shown that unlike normal skin, which is slightly acidic, the pH of the wound microenvironment is alkaline, which can lead to a decrease in the α-helix content in the antimicrobial peptide, and a decrease in solubility and antimicrobial properties. Therefore, the main challenge faced by the application of the antimicrobial peptide LL37 is the decrease in its activity and antimicrobial efficacy in the wound environment.
[0005] Metal-organic frameworks (MOFs) are a new type of organic-inorganic composite material with excellent properties that cannot be matched by traditional porous materials, such as high specific surface area, clear crystal structure, adjustable pore size and shape, variable structure, and post-modification. At present, there have been reports on the immobilization of biomolecules (such as enzymes) in MOFs structures for biocatalysis, sensing, separation, and imaging. However, due to the certain cytotoxicity of metal ions and organic ligands in MOFs and their strong adaptability to biomolecules of different molecular weights and spatial structures, there are currently few types of MOFs materials suitable for the medical field. For biomolecules with large molecular weight, complex structure, and poor stability, there are great technical challenges and uncertainties in designing and synthesizing "customized" MOFs with clear structure and excellent biocompatibility to achieve high encapsulation rate of biomolecules and form biomolecule@MOFs complexes to achieve the goal of ensuring the activity of biomolecules while improving their tolerance to the external environment. Furthermore, there are great unknowns and unpredictabilities in screening and optimizing the excipient composition and preparation process conditions that are compatible with the biomolecule@MOFs complex to achieve effective delivery of biomolecules to the site of action to ensure their efficacy and safety.
[0006] In addition, whether it is the reported LL37 viscous liquid or the wound repair or wound healing preparations that have been marketed, their dosage forms are mostly solutions, gels, ointments, creams, etc., which have the following defects in clinical application: solution-type preparations are either sprayed for administration, resulting in unnecessary waste of liquid medicine flowing on the wound, or the liquid medicine is soaked in gauze and then bandaged on the wound, resulting in adhesion, while room temperature semi-solid preparations such as gels are applied for administration, which can easily cause discomfort to patients (for example: increased pain). Therefore, a milder and more reasonable administration method is urgently needed to improve the convenience of clinical medication and patient tolerance. Summary of the invention
[0007] In view of this, the present invention provides a LL37@ZPF-2 complex, a pharmaceutical composition and an application. The LL37@ZPF-2 complex provided by the present invention has better antibacterial efficacy, cell migration effect and wound healing effect than LL37, and has good biocompatibility.
[0008] In the first aspect, the present invention provides a LL37@ZPF-2 complex, comprising a metal organic framework material ZFP-2 and an antimicrobial peptide LL37 loaded on ZFP-2; wherein the organic ligand in the ZFP-2 is 2-hydroxy-5-fluoropyrimidine, and the metal ion is Zn 2+ ; The loading amount of LL37 is 0.05~0.3g / g.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned LL37@ZPF-2 complex, comprising the following steps:
[0010] The LL37 aqueous solution is added to the 2-hydroxy-5-fluoropyrimidine aqueous solution, and then the zinc salt aqueous solution is added, stirred evenly and allowed to stand for reaction; the solid product obtained by the reaction is then washed and dried to obtain the LL37@ZPF-2 complex.
[0011] Preferably, the concentration of the LL37 aqueous solution is 1 to 10 mg / mL; the concentration of the 2-hydroxy-5-fluoropyrimidine is 12 to 20 mg / mL; and the concentration of the zinc salt aqueous solution is 10 to 25 mg / mL.
[0012] Preferably, Zn in the 2-hydroxy-5-fluoropyrimidine and zinc salt 2+ The molar ratio is (2.8-3.2):1; the mass ratio of LL37 and 2-hydroxy-5-fluoropyrimidine is (0.2-2):(5-8).
[0013] Preferably, the zinc salt is selected from one or more of zinc nitrate, zinc chloride, zinc sulfate, zinc acetate or zinc gluconate.
[0014] Preferably, the static reaction time is 20 to 60 minutes, and the static reaction temperature is 10 to 40°C.
[0015] In a third aspect, the present invention provides a pharmaceutical composition comprising the above-mentioned LL37@ZPF-2 complex or the LL37@ZPF-2 complex prepared by the above-mentioned preparation method and a poloxamer 407 gel solution.
[0016] Preferably, in the poloxamer 407 gel solution, the concentration of poloxamer 407 is 15-18wt%, and the solvent of the poloxamer 407 gel solution is selected from any one of citrate buffer, phosphate buffer or water; the dosage ratio of the LL37@ZPF-2 complex and the poloxamer 407 gel solution is (0.5-3.5) mg:1 mL.
[0017] Preferably, the pharmaceutical composition is administered by spraying.
[0018] In a fourth aspect, the present invention provides the use of the above-mentioned LL37@ZPF-2 complex or the LL37@ZPF-2 complex prepared by the above-mentioned preparation method or the above-mentioned pharmaceutical composition in the preparation of a drug for promoting wound healing.
[0019] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0020] (1) The LL37@ZPF-2 composite provided by the present invention has better antibacterial effect and wound healing effect than LL37, can effectively inhibit bacterial growth and reduce the risk of wound infection; and has good biocompatibility and high safety; in addition, the LL37@ZPF-2 composite has better thermal stability than the existing LL37 solid powder, and can be stably stored at 25°C / 60%RH for at least 6 months, while LL37 needs to be stored at low temperature.
[0021] (2) The preparation method of the LL37@ZPF-2 complex provided by the present invention is very simple, does not require long-term high-temperature treatment, has low energy consumption, and has a high LL37 encapsulation rate.
[0022] (3) The pharmaceutical composition provided by the present invention not only has good antibacterial and wound healing effects, but also has higher application convenience and patient compliance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 is the powder X-ray diffraction pattern of ZPF-2 of the present invention and the LL37@ZPF-2 composite of Example 1;
[0025] Figure 2 is a transmission electron microscope image of the ZPF-2 of the present invention and the LL37@ZPF-2 complex of Example 1;
[0026] Figure 3 It is a laser confocal image of ZPF-2 of the present invention (i) and the FITC-LL37@ZPF-2 complex of Example 1 (ii);
[0027] Figure 4 is the release curve of the LL 37@ZPF-2 complex of Example 1 of the present invention;
[0028] Figure 5 It is an agar plate coating picture of the PBS group, LL37 group, LL37 thermosensitive gel group (LL37@Gel), LL37@ZPF-2 group and LL37@ZPF-2 thermosensitive gel group (LL37@ZPF-2Gel) in the test examples of the present invention;
[0029] Figure 6is the cell survival rate of the PBS group, LL37 group, LL37 thermosensitive gel group (LL37@Gel), LL37@ZPF-2 group and LL37@ZPF-2 thermosensitive gel group (LL37@ZPF-2Gel) in the test examples of the present invention;
[0030] Figure 7 It is a graph showing the results of the cell scratch test of the PBS group, the LL37 group, the LL37 thermosensitive gel group (LL37@Gel), the LL37@ZPF-2 group, and the LL37@ZPF-2 thermosensitive gel group (LL37@ZPF-2Gel) in the test examples of the present invention;
[0031] Figure 8 It is the blood compatibility test of the PBS group, LL37 group, LL37 thermosensitive gel group (LL37@Gel), LL37@ZPF-2 group and LL37@ZPF-2 thermosensitive gel group (LL37@ZPF-2Gel) in the test examples of the present invention;
[0032] Fig. 9 It is a diagram of the wound healing process of the PBS group, the LL37 group, the LL37 thermosensitive gel group (LL37@Gel), the LL37@ZPF-2 group, and the LL37@ZPF-2 thermosensitive gel group (LL37@ZPF-2Gel) in the test examples of the present invention;
[0033] Fig.10 is the wound healing rate after treatment with PBS group, LL37 group, LL37 thermosensitive gel group (LL37@Gel), LL37@ZPF-2 group and LL37@ZPF-2 thermosensitive gel group (LL37@ZPF-2Gel) in the test examples of the present invention;
[0034] Fig.11 HE-stained skin tissue sections of the PBS group, LL37 group, LL37 thermosensitive gel group (LL37@Gel), LL37@ZPF-2 group, and LL37@ZPF-2 thermosensitive gel group (LL37@ZPF-2Gel) in the test examples of the present invention (the yellow line indicates the boundary between the epithelium and the dermis; the red arrow indicates the blood vessel; the green arrow indicates the hair follicle);
[0035] Fig.12 These are Masson trichrome-stained wound photographs of the PBS group, LL37 group, LL37 thermosensitive gel group (LL37@Gel), LL37@ZPF-2 group, and LL37@ZPF-2 thermosensitive gel group (LL37@ZPF-2Gel) in the test examples of the present invention. DETAILED DESCRIPTION
[0036] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0037] The present invention provides an LL37@ZPF-2 complex, comprising a metal organic framework material ZFP-2 and an antimicrobial peptide LL37 loaded on ZFP-2; wherein the organic ligand in the ZFP-2 is 2-hydroxy-5-fluoropyrimidine, and the metal ion is Zn 2 + ; The loading amount of LL37 is 0.05~0.3g / g.
[0038] The antimicrobial peptide LL37 of the present invention is preferably provided in the form of acetate, and other salts may also be used.
[0039] The present invention finds that when the metal organic framework material ZFP-2 is used as a carrier material, not only can the antibacterial effect of LL37 and the wound healing effect be enhanced, but it also has good biocompatibility.
[0040] The present invention provides a method for preparing the above-mentioned LL37@ZPF-2 complex, comprising the following steps:
[0041] The LL37 aqueous solution is added to the 2-hydroxy-5-fluoropyrimidine aqueous solution, and then the zinc salt aqueous solution is added, stirred evenly and allowed to stand for reaction; the solid product obtained by the reaction is then washed and dried to obtain the LL37@ZPF-2 complex.
[0042] In the present invention, the concentration of the LL37 aqueous solution is 1-10 mg / mL; the concentration of the 2-hydroxy-5-fluoropyrimidine is 12-20 mg / mL; and the concentration of the zinc salt aqueous solution is 10-25 mg / mL.
[0043] In the present invention, the Zn in the 2-hydroxy-5-fluoropyrimidine and zinc salt is 2+ The molar ratio is (2.8-3.2):1; the mass ratio of LL37 and 2-hydroxy-5-fluoropyrimidine is (0.2-2):(5-8), and more preferably (0.4-1):(6-8).
[0044] The present invention does not impose any special restrictions on the source of 2-hydroxy-5-fluoropyrimidine. A commercially available product can be directly used or prepared by reaction. The present invention preferably uses 2-chloro-5-fluoropyrimidine and a hydroxide to obtain the product, wherein the hydroxide is selected from sodium hydroxide, potassium hydroxide or lithium hydroxide, preferably sodium hydroxide. A more preferred preparation method is: dissolving 2-chloro-5-fluoropyrimidine and NaOH in a mass ratio of (3 to 3.5):1 in an appropriate amount of water, reacting at room temperature for 48 to 72 hours, and then adjusting the pH value of the reaction solution to 8.0 to 9.0, and obtaining 2-hydroxy-5-fluoropyrimidine after rotary evaporation.
[0045] In the present invention, the zinc salt is selected from one or more of zinc nitrate, zinc chloride, zinc sulfate, zinc acetate or zinc gluconate, and hydrated salts of the above zinc salts may also be used.
[0046] The present invention does not impose any special restrictions on the rotation speed and time for uniform stirring. In the present invention, the time of the static reaction is 20 to 60 minutes, the temperature of the static reaction is 10 to 40°C, and the static reaction can be carried out at room temperature without heating or cooling. The method of the present invention can achieve precise assembly of ZPF-2 and effective encapsulation of LL37 to form a stable LL37@ZPF-2 complex under mild conditions of room temperature aqueous phase. The method can achieve a maximum LL37 encapsulation rate of more than 90%.
[0047] The present invention does not impose any special restrictions on the acquisition of solid products, and the solid-liquid separation methods in the prior art can be used, such as centrifugation, filtration, suction filtration, etc. The present invention does not impose any special restrictions on the washing and drying processes, and the present invention preferably uses water for multiple washings and then freeze-drying.
[0048] The present invention also provides a pharmaceutical composition, comprising the above-mentioned LL37@ZPF-2 complex or the LL37@ZPF-2 complex prepared by the above-mentioned preparation method and a poloxamer 407 gel solution.
[0049] In the present invention, the concentration of poloxamer 407 in the poloxamer 407 gel solution is 15-18wt%, too low a concentration will result in too long a gelation time, too high a concentration will not allow spray administration; more preferably 17-18wt%. The solvent of the poloxamer 407 gel solution is selected from any one of citrate buffer, phosphate buffer or water; the dosage ratio of the LL37@ZPF-2 complex and the poloxamer 407 gel solution is (0.5-3.5) mg:1 mL, more preferably (1-2) mg:1 mL; this concentration range may vary depending on the individual user, and the adjustment of the concentration of the LL37@ZPF-2 complex in the poloxamer 407 gel solution also falls within the scope of protection of the present invention.
[0050] The present invention does not impose any particular limitation on the preparation method of the poloxamer 407 gel solution. The present invention preferably comprises weighing poloxamer 407, adding the solution to a solvent, stirring and dispersing the solution uniformly, placing the solution at 4 to 8° C. to obtain a colorless, clear, uniformly dispersed gel solution, sterilizing the solution at 121° C. for 15 to 30 minutes, cooling the solution to room temperature, and then restoring the solution to a uniform state at 4 to 8° C.
[0051] In the present invention, the administration route of the pharmaceutical composition is spray administration. The pharmaceutical composition provided by the present invention is in liquid state below 25°C. When administered by spraying, the liquid droplets will quickly change into a solid-like gel state after contacting the wound surface, which is more effective in adhering to the wound surface, improving the backward administration method of existing wound repair drugs, and improving the convenience of clinical administration of such preparations and patient compliance.
[0052] The pharmaceutical composition of the present invention is packaged separately from the LL37@ZPF-2 complex and the poloxamer 407 gel solution during storage and transportation, and is prepared immediately before use, that is, LL37@ZPF-2 is added to the sterile blank thermosensitive gel at a temperature below 25°C, mixed evenly, and then added to a spray bottle for use. This can maximize the stability of LL37@ZPF-2 and save the storage and transportation costs of drugs and preparations.
[0053] The pharmaceutical composition of the present invention also includes other pharmaceutically acceptable carriers and adjuvants, which are not particularly limited in the present invention.
[0054] The present invention also provides the use of the above-mentioned LL37@ZPF-2 complex or the LL37@ZPF-2 complex prepared by the above-mentioned preparation method or the above-mentioned pharmaceutical composition in the preparation of a drug for promoting wound healing.
[0055] The wound healing promoting drugs of the present invention include but are not limited to drugs for treating burn wounds, chronic wounds, and fresh wounds. The drugs for treating burn wounds include but are not limited to drugs for treating superficial II degree, deep II degree, and granulation wounds. The drugs for treating chronic wounds include but are not limited to drugs for treating chronic granulation wounds, ulcers, and bedsores. The drugs for treating fresh wounds include but are not limited to drugs for treating trauma and surgical injuries.
[0056] The technical solution of the present invention is further described below in conjunction with specific examples. The present invention has no particular restrictions on the source of the reagents used in the following examples, and commercial products known to those skilled in the art can be used. LL37 is provided in the form of acetate.
[0057] In the following example, ZPF-2 was synthesized by the following steps: 0.4 mL of zinc nitrate hexahydrate (14.9 mg / mL) was added to 0.4 mL of 2-hydroxy-5-fluoropyrimidine aqueous solution (17.3 mg / mL), stirred evenly at room temperature (25±3°C), and allowed to react for 30 minutes. The reaction solution was centrifuged at 9000 rpm, and the precipitate was washed three times with distilled water and freeze-dried to obtain ZPF-2.
[0058] Example 1
[0059] This example provides a synthesis of a LL37@ZPF-2 complex.
[0060] (1) 1.59 g of 2-chloro-5-fluoropyrimidine and 0.48 g of NaOH were dissolved in 240 mL of distilled water, and the mixture was reacted at room temperature at a rotation speed of 1200 rpm for 48 h. The pH value of the reaction solution was then adjusted to 8.5 with 5 M HCl, and 2-hydroxy-5-fluoropyrimidine was obtained after rotary evaporation.
[0061] (2) 0.2 mL of LL37 aqueous solution (2.5 mg / mL) was added to 0.4 mL of 2-hydroxy-5-fluoropyrimidine aqueous solution (17.3 mg / mL), and then 0.4 mL of zinc nitrate hexahydrate (14.9 mg / mL) was added. After stirring evenly, the solution was allowed to react at room temperature (25±3°C) for 30 minutes. The reacted solution was centrifuged at 9000 rpm, and the precipitate was washed three times with distilled water and freeze-dried to obtain the LL37@ZPF-2 complex.
[0062] Figure 1 is the powder X-ray diffraction pattern of ZPF-2 and LL37@ZPF-2 of this example. The results show that after loading LL37, the PXRD spectrum of LL37@ZPF-2 is consistent with the simulated structure, indicating that the expected high crystallinity structure has been formed.
[0063] Figure 2 Figure 1 is the TEM (transmission electron microscope) image of ZPF-2 and LL37@ZPF-2 of this example. The results show that ZPF-2MOFs has high crystallinity and a uniform hexagonal morphology. The crystal morphology and average size of LL37@ZPF-2 and ZPF-2 are similar, but the surface of LL37@ZPF-2 is relatively rough, the edges and corners disappear and become elliptical, which indicates that LL37 has been successfully loaded into ZPF-2.
[0064] Figure 3 The laser confocal images of ZPF-2 and FITC-LL37@ZPF-2 (FITC was labeled on LL37) showed that ZPF-2 without FITC-LL37 showed no green fluorescence, while Figure 3(ii) in the figure clearly shows that ZPF-2 containing FITC-LL37 has strong green fluorescence and exhibits more uniform dispersion, indicating that LL37 is uniformly loaded into ZPF-2.
[0065] Example 2
[0066] The difference between this embodiment and embodiment 1 is that the concentration of the LL37 aqueous solution is 10 mg / mL.
[0067] Example 3
[0068] The difference between this embodiment and embodiment 1 is that the concentration of the LL37 aqueous solution is 5 mg / mL.
[0069] Example 4
[0070] The difference between this embodiment and embodiment 1 is that the concentration of the LL37 aqueous solution is 1 mg / mL.
[0071] Example 6
[0072] This embodiment provides a method for preparing a LL37@ZPF-2 thermosensitive gel (LL37@ZPF-2Gel).
[0073] (1) Weigh 18% (w / w) poloxamer 407 and add it to 82% (w / w) 50mM pH 5.0 citric acid-sodium citrate buffer, stir and disperse it evenly, and place it in a refrigerator at 4-8°C for 24 hours to completely dissolve it, to obtain a colorless, clear, and evenly dispersed gel solution. Then, sterilize the poloxamer 407 gel solution at 121°C for 15 minutes, cool it to room temperature, and place it in a refrigerator at 4-8°C to restore it to a colorless, clear, and evenly dispersed solution, i.e., the poloxamer 407 blank gel solution.
[0074] (2) At 20±3°C, 12 mg of LL37@ZPF-2 (containing 1.8 mg of LL37) of Example 1 was accurately weighed and uniformly dispersed in 10 mL of poloxamer 407 blank gel solution. A semisolid gel was obtained at a temperature above 28°C, namely, LL37@ZPF-2 thermosensitive gel, denoted as LL37@ZPF-2Gel. The concentration of LL37 in the thermosensitive gel was 0.18 mg / mL.
[0075] Example 7
[0076] The difference between this embodiment and embodiment 6 is that the solvent of the poloxamer 407 blank gel solution is 10 mM pH 7.4 PBS buffer.
[0077] Example 8
[0078] The difference between this embodiment and embodiment 6 is that the solvent of the blank gel solution of poloxamer 407 is water.
[0079] Example 9
[0080] The difference between this embodiment and embodiment 6 is that the concentration of poloxamer 407 in the poloxamer 407 blank gel solution is 17% (w / w).
[0081] Example 10
[0082] The difference between this embodiment and embodiment 9 is that the solvent of the poloxamer 407 blank gel solution is 10 mM pH 7.4 PBS buffer.
[0083] Embodiment 11
[0084] The difference between this embodiment and embodiment 9 is that the solvent of the blank gel solution of poloxamer 407 is water.
[0085] Test example
[0086] 1. Determination of the encapsulation efficiency of ZPF-2 for LL37 and the loading amount of LL37 in the LL37@ZPF-2 complex
[0087] (1) Encapsulation efficiency of ZPF-2 for LL37
[0088] Methods: The concentration of LL37 was determined by the Bradford method. Accurately add 20 μL of the test solution to a 96-well plate, then add 200 μL of Bradford solution to each well, and immediately collect the absorbance at a wavelength of 595 nm. According to this model, a calibration curve with a LL37 concentration of 0 to 0.2 mg / mL was drawn. The encapsulation efficiency of LL37 in the LL37@ZPF-2 complex was determined by measuring the remaining amount of unencapsulated LL37 in the supernatant after the formation of the complex, that is, encapsulated LL37 = initial LL37 - unencapsulated LL37. The encapsulation efficiency of LL37 was calculated using the following formula:
[0089]
[0090] (2) LL37 loading in LL37@ZPF-2 complex
[0091] Method: The loading amount is the ratio of the mass of LL37 loaded in LL37@ZPF-2 to the total mass of LL37@ZPF-2.
[0092] The test results are shown in Table 1.
[0093] Table 1 Encapsulation efficiency and loading amount of LL37 in LL37@ZPF-2 complexes of Examples 1 to 4
[0094] serial number LL37 concentration (mg / mL) Encapsulation efficiency Loading capacity (g / g) Example 2 10 62.5% 0.275 Example 3 5 89.9% 0.197 Example 1 2.5 92.5% 0.15 Example 4 1 100% 0.05
[0095] 2. Determination of LL37 release rate in LL37@ZPF-2
[0096] Method: The lyophilized powder of the LL37@ZPF-2 complex of Example 1 was weighed and dissolved in 100 mM citric acid-sodium citrate buffer at pH = 5.0 at room temperature to a concentration of 1 mg / mL. After centrifugation at 8000 rpm for 1 minute at each time point, the supernatant was extracted and the content of LL37 was detected by Bradford method. Figure 4 The results showed that the LL37@ZPF-2 complex could quickly release LL37 within 30 minutes and completely release it in about 2 hours.
[0097] 3. Determination of gel phase transition temperature and skin gelation time
[0098] Method: Take 1 mL of the blank gel solution of poloxamer 407 of Example 6 and Example 7 below 25°C in 10 mL stoppered graduated test tubes, place them in a water bath and slowly heat them up, and use a precision thermometer with an accuracy of 0.1°C to measure the phase transition temperature from solution to gel, i.e., the gelation temperature. The criterion is that the test tube is inverted for 10 seconds and no gel flows in the test tube. In order to determine the gelation time of the thermosensitive gel on the skin, the gel solution is placed in a vacuum spray bottle below 25°C, and the time to form a semi-solid gel after spraying on the skin surface is observed. After each bottle is sprayed 3 times, the timing starts, and the time when the gel changes from liquid to semi-solid and stops flowing is used as the standard.
[0099] The results are shown in Table 2.
[0100] Table 2 Related indicators of Poloxamer 407 blank gel of Examples 6 to 7
[0101]
[0102] Note: The pH value of gel is determined directly using a pH meter.
[0103] The relevant indicators of the LL37@ZPF-2 thermosensitive gel of Example 6 were determined by the same method, as shown in Table 3.
[0104] Table 3 Related indicators of LL37@ZPF-2 thermosensitive gel of Example 6
[0105] Characteristics LL37@ZPF-2 Thermosensitive Gel Characteristics Milky white translucent gel Gel pH 5.40 Gelation temperature (℃) 27.6 Skin gel time (s) 5s, spray out in mist
[0106] The results showed that the blank gel of poloxamer 407 and the thermosensitive gel of LL37@ZPF-2 with a mass concentration of 17% and 18% could be administered by spraying and could quickly phase-change into a gel state on the skin. The solvents could be citrate buffer, phosphate buffer or water.
[0107] 4. Minimum bactericidal concentration (MBC) and minimum inhibitory concentration (MIC) test
[0108] Method: The antibacterial properties (MBC and MIC) of LL37 and the LL37@ZPF-2 complex of Example 1 against common wound infection bacteria, Staphylococcus aureus and Escherichia coli, were tested. Staphylococcus aureus was cultured in a shaker at 37°C overnight, and then the Staphylococcus aureus solution was diluted to 1×10 6 CFU / mL. Add 1×10 6 CFU / mL Staphylococcus aureus dilution, 100μL per well. Double dilution concentration test of LL37 was performed with sterile LB liquid medium, with a concentration range of 1 to 16μM, and 100μL was added to the well for each concentration. LL37@ZPF-2 was also tested according to the above concentration and dilution method. The bacterial solution and the sample solution to be tested were added to a 96-well plate, and then moved to a 37℃ incubator for 16 hours, and the OD was recorded. 600 Take 50 μL of the mixture from the well and spread it evenly on the sterile solidified LB solid medium, continue to culture in a 37°C incubator for 18 hours, observe and record the phenomenon.
[0109] The method for determining the antibacterial activity against E. coli was the same as that for S. aureus, with the only difference being that the concentrations of LL37 and LL37@ZPF-2 were changed to 2 to 64 μM.
[0110] The results are shown in Table 4.
[0111] Table 4 MBC and MIC of LL37 and LL37@ZPF-2 of Example 1
[0112]
[0113] The results showed that LL37 had a higher inhibitory effect on Staphylococcus aureus than Escherichia coli. The MBC required to inhibit Staphylococcus aureus was 4 μmol / L, while the MBC of LL37 against Escherichia coli was 32 μmol / L. The fixation and encapsulation of LL37 by ZPF-2 significantly improved the antibacterial effect of LL37, thereby reducing the concentration required to inhibit Staphylococcus aureus and Escherichia coli.
[0114] 5. Determination of antibacterial properties
[0115] Methods: In order to observe the antibacterial ability of different groups, the agar plate method was used to detect bacterial proliferation and evaluate the bactericidal effect. The experimental groups were divided into PBS group, LL37 group, LL37 thermosensitive gel group, LL37@ZPF-2 group, and LL37@ZPF-2 thermosensitive gel group. The concentration of LL37 in the LL37 group, LL37 thermosensitive gel group, LL37@ZPF-2 group, and LL37@ZPF-2 thermosensitive gel group was 0.18 mg / mL; LL37 group and LL37@ZPF-2 group used citric acid-sodium citrate buffer (pH=5.0) as solvent; LL37@ZPF-2 group and LL37@ZPF-2 thermosensitive gel group LL37@ZPF-2 complex prepared in Example 1. LL37@ZPF-2 thermosensitive gel was prepared according to the preparation method of LL37@ZPF-2 thermosensitive gel in Example 6, and LL37 thermosensitive gel was prepared in the same way.
[0116] Staphylococcus aureus was cultured in a shaker at 37 °C overnight and then diluted to 1 × 10 6 CFU / mL. Add 1×10 6 CFU / mL Staphylococcus aureus dilution, 100μL per well. Double dilution concentration test was performed on the above LL37, LL37 thermosensitive gel, LL37@ZPF-2, and LL37@ZPF-2 thermosensitive gel using sterile LB liquid culture medium, with a concentration range of 1 to 16μM, and 100μL was added to the well for each concentration. The bacterial solution and the sample solution to be tested were added to a 96-well plate, and then moved to a 37℃ incubator for incubation for 16 hours. Take 50μL of the mixture from the well and evenly spread it on the sterile solidified LB solid culture medium, and continue to incubate in a 37℃ incubator for 18 hours, observing and recording the phenomenon.
[0117] Figure 5 The agar plate coating pictures of the PBS group, LL37 group, LL37 thermosensitive gel group (LL37@Gel), LL37@ZPF-2 group and LL37@ZPF-2 thermosensitive gel group (LL37@ZPF-2Gel) show that a large number of bacteria were observed on the agar plate of the PBS control group, while the number of bacteria decreased after treatment with LL37 and LL37@ZPF-2. The number of bacteria observed on the agar plate of the LL37@ZPF-2 thermosensitive gel group was significantly less than that of the LL37 thermosensitive gel group, indicating that the LL37@ZPF-2 thermosensitive gel can be used as an effective antibacterial therapeutic agent.
[0118] 6. Cytocompatibility
[0119] Methods: L929 mouse fibroblasts were used for co-incubation experiments to evaluate the cell compatibility of LL37@ZPF-2 and LL37@ZPF-2 thermosensitive gel. Samples were prepared by aseptic operation. The experimental groups were divided into PBS group, LL37 group, LL37@ZPF-2 group, LL37 thermosensitive gel group and LL37@ZPF-2 thermosensitive gel group. The LL37@ZPF-2 group and LL37@ZPF-2 thermosensitive gel group used the LL37@ZPF-2 complex of Example 1, and the LL37@ZPF-2 thermosensitive gel was prepared by the LL37@ZPF-2 thermosensitive gel preparation method of Example 6. The LL37 thermosensitive gel was prepared by the same method. The concentration of LL37 in the LL37 group, LL37@ZPF-2 group, LL37 thermosensitive gel group and LL37@ZPF-2 thermosensitive gel group was 20 μg / mL. The complete medium without any therapeutic drug was used as the control group, and the drug-treated group was co-cultured with the complete medium. After 24 hours of co-culture, 20 μL of MTT solution (5 μg / mL) was added to the culture medium, protected from light, and reacted for 4 hours. After discarding the culture medium, 150 μL of DMSO solution was added, protected from light, and then shaken on a well plate shaker for 20 minutes, and then the OD value was measured at a wavelength of 490 nm or 570 nm using a microplate reader.
[0120] MTT assay showed that LL37@ZPF-2 thermosensitive gel did not affect the survival rate of L929 cells. Figure 6 As shown, after culturing in the extract for 24 h, the cell survival rate of each experimental group was over 90%, which indicated that the composite hydrogel had good biocompatibility.
[0121] 7. Cell Migration Assessment
[0122] The cell migration of mouse L929 fibroblasts was determined by cell scratch method. The experimental groups were the same as those in the above cell compatibility experiments. 5 The cells were inoculated into a 6-well plate at a density of 100 cells / well. After one day of culture, the bottom of the plate was covered with a single layer of cells. Then, the cells were scraped in a straight line with a pipette tip. After rinsing with PBS, the drug-containing culture medium of each group was added to the well plate in contact with the scraped cell layer, and the fetal bovine serum content in each group of culture medium was 0.1%. Each group of cells was cultured in the culture medium for one day. The cells were observed under an optical microscope. The cell migration rate was calculated according to the following formula:
[0123]
[0124] The initial wound surface after scratching was designated as S0, and the wound surface after 24 hours was designated as S t .
[0125] Figure 7The results showed that there were significant differences in the migration degree of cell scratches after different treatments. After 24 hours of co-culture, the cell migration rates of the LL37@ZPF-2 group, the LL37 thermosensitive gel group, and the LL37@ZPF-2 thermosensitive gel group increased significantly compared with the control group, among which the cell migration rate of LL37@ZPF-2 was 64.5% faster than that of the control group. These results show that the LL37@ZPF-2 thermosensitive gel group has the ability to promote cell migration and has great application potential in promoting wound healing.
[0126] 8. In vitro hemolysis test
[0127] Methods: Anticoagulated rabbit blood was mixed with PBS at a ratio of 1:4 (v:v), and then centrifuged at 3000 rpm for 15 minutes to obtain red blood cells. The red blood cell solution was mixed with PBS at a ratio of 1:9 (v:v) to form a red blood cell suspension. As the experimental group, 500 μL of red blood cell suspension was added to 500 μL of hydrogel. The solution obtained by mixing deionized water with red blood cells at a ratio of 1:1 (v:v) and the red blood cell suspension without sample were used as the positive control group and the negative control group, respectively. The experimental group was grouped in the same way as the cell compatibility experiment. After incubation at 37°C for 1 hour, the mixture was centrifuged at 2000 rpm for 15 minutes, and the supernatant of each group was collected. The absorbance of the supernatant at 540 nm was measured by an enzyme marker, and the hemolysis rate was calculated according to the following formula.
[0128]
[0129] Figure 8 The results showed that the supernatant of all experimental groups was clear after centrifugation, and the red blood cells were precipitated at the bottom of the EP tube, which was consistent with the negative control group, while the red blood cells of the positive control group were lysed and the supernatant was also red. The quantitative results showed that the hemolysis rate of all hydrogels was less than 5%, indicating that the hydrogels have good blood compatibility, which is within the allowable range for the application of medical biomaterials.
[0130] 9. Wound healing experiment and histological analysis
[0131] Methods: The wound healing of SD rats (male, 6-8 weeks old) was evaluated in a full-thickness skin defect model. Twenty-five SD rats were selected and equally divided into five experimental groups, namely, control group (PBS), LL37 group, LL37@ZPF-2 group, LL37 thermosensitive gel group (LL37@Gel for short), and LL37@ZPF-2 thermosensitive gel group (LL37@ZPF-2Gel for short), and they were given 3 days of adaptive training before surgery. Among them, the concentration of LL37 in the LL37 group, LL37@ZPF-2 group, LL37 thermosensitive gel group and LL37@ZPF-2 thermosensitive gel group was 0.18 mg / mL; the LL37 group and LL37@ZPF-2 group used citric acid-sodium citrate buffer (pH=5.0) as solvent; the LL37@ZPF-2 used was the LL37@ZPF-2 complex of Example 1; the LL37@ZPF-2 thermosensitive gel was prepared according to the LL37@ZPF-2 thermosensitive gel preparation method of Example 6, and the LL37 thermosensitive gel was prepared by the same method.
[0132] Rats were anesthetized with 7% sodium pentobarbital to construct a wound infection model. After depilation of the back skin, a full-circle skin defect was created using an 8 mm diameter punch and curved scissors, and Staphylococcus aureus (1×10 5 CFU / mL, 50μL) to infect the wound. Then the wounds were treated with 100μL PBS group, LL37 group, LL37@ZPF-2 group, LL37@Gel group and LL37@ZPF-2Gel group, respectively. On days 0, 3, 7, 10 and 14, wound images were taken, and Image J software was used to determine the wound area and analyze the wound healing. On days 3, 7 and 14, some tissue samples around the wound were collected, fixed and embedded. Each section was stained with hematoxylin-eosin. The rats were killed at the predetermined time points (3, 7, and 14 days). The local skin on the back of the rats was incised, the degradation of the hydrogel was observed and recorded, and all the excised tissues were immediately fixed in a paraformaldehyde solution to ensure the stability of the cell structure and prevent degeneration. After collecting all component samples, the tissue was stained with hematoxylin-eosin. The stained tissue sections were carefully observed and recorded under a microscope to analyze the hydrogel tissue repair process.
[0133] Fig. 9 and Fig.10The results showed that LL37@ZPF-2 thermosensitive gel can effectively promote wound healing. The PBS group served as the control group. After 3 days of treatment, the wounds of all experimental groups were reduced, and the wound area of the LL37@ZPF-2 thermosensitive gel group was reduced to 71.0±0.7%. On the 7th day, the wound area of the LL37@ZPF-2 thermosensitive gel group was significantly reduced, and the wound healing rate was 94.4±0.6%, which was higher than that of the control group (71.22±0.9%). The wounds of the LL37@ZPF-2 thermosensitive gel group were almost completely healed on the 10th day, and the wounds were covered with new epithelium, while the wounds of the control group were still not healed. On the 14th day, the wounds of the LL37@ZPF-2 group and the LL37@ZPF-2 thermosensitive gel group were completely healed and covered with hair. The results also showed that ZPF-2-encapsulated LL37 has higher stability, can inhibit bacterial growth, and promote tissue regeneration.
[0134] HE staining was performed on wound tissues of five groups of rats infected with Staphylococcus aureus to evaluate the healing and regeneration process after 14 days. Normally, inflammatory cells (such as neutrophils and lymphocytes) appear blue in HE staining, while the extracellular matrix and cytoplasm appear pink in varying shades. Fig.11 As shown in the figure, the skin tissues of rats in each group had different degrees of damage on the 3rd day. Compared with the LL37@ZPF-2 thermosensitive gel group, the epidermal and dermal structures of rats in the control group were still significantly defective, and a large number of inflammatory cells were visible. On the 7th day, the LL37@ZPF-2 thermosensitive gel group began to have new epithelial tissue and many granulation tissues, while no epithelial tissue was formed in the other groups. On the 14th day, all groups had obvious new epidermis and dermis, and some skin accessory structures, while the wound surface of the LL37@ZPF-2 thermosensitive gel group was close to the natural tissue, the epidermis in the regenerated area was uniform and flat, the thickness and structure of the dermis were similar to the normal structure, and the hair follicles were arranged evenly and neatly. Therefore, the LL37@ZPF-2 thermosensitive gel group had the best effect in promoting the healing of wounds infected with Staphylococcus aureus by reducing the inflammatory response and promoting epithelialization.
[0135] The total collagen content of the hydrogels in the neojoint tissue was assessed using Masson's trichrome staining. Fig.12 As shown, collagen is stained blue and keratin or muscle fibers are stained red. After 7 days, collagen deposition appeared on the wound surface, and collagen fibers were infiltrated in all groups, but the collagen fibers in the LL37@ZPF-2 thermosensitive gel group were denser and more orderly. Some fibrous tissue hyperplasia and neovascularization were also observed in the LL37@ZPF-2 thermosensitive gel group. On the 14th day, the collagen expression in the LL37@ZPF-2 thermosensitive gel group was the highest, and the dermal collagen fibers were arranged more orderly, which was basically consistent with the normal skin structure. The results show that LL37@ZPF-2 thermosensitive gel can reshape the wound by promoting collagen deposition.
[0136] 10. LL37@ZPF-2 stability
[0137] Method: The LL37 and LL37@ZPF-2 solid powders of Example 1 were placed at 60°C for 15 days and 25°C / RH60% for 6 months, respectively. The Bradford method was used to determine the LL37 content in the LL37 and LL37@ZPF-2 composites after 0 day, 15 days at 60°C, and 6 months at 25°C / RH 60%, and the content change rate was calculated, as shown in Table 5.
[0138] Table 5 LL37@ZPF-2 stability test results
[0139] Sample name LL37 LL37@ZPF-2 complex Day 0 100% 12.0% 60℃, 15 days 90.1% 11.8% LL37 content change rate at 60℃ -9.9% -1.7% 25℃ / RH60%, 6 months 73.3% 11.1% LL37 content change rate at 25℃ / RH60% -26.7% -7.5%
[0140] The results show that LL37@ZPF-2 has significantly improved thermal stability compared to LL37. The solid powder can be stable for at least 6 months in an environment of 25℃ / RH60%, and can be stored, transported and used at room temperature below 25℃.
[0141] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A LL37@ZPF-2 complex, characterized in that: The invention comprises a metal organic framework material ZFP-2 and an antimicrobial peptide LL37 loaded on ZFP-2; wherein the organic ligand in the ZFP-2 is 2-hydroxy-5-fluoropyrimidine, and the metal ion is Zn 2+ ; The loading amount of LL37 is 0.05~0.3g / g.
2. The method for preparing the LL37@ZPF-2 complex according to claim 1, characterized in that: The steps include: The LL37 aqueous solution is added to the 2-hydroxy-5-fluoropyrimidine aqueous solution, and then the zinc salt aqueous solution is added and allowed to react; the solid product obtained by the reaction is then washed and dried to obtain the LL37@ZPF-2 complex.
3. The preparation method according to claim 2, characterized in that: The concentration of the LL37 aqueous solution is 1-10 mg / mL; the concentration of the 2-hydroxy-5-fluoropyrimidine is 12-20 mg / mL; and the concentration of the zinc salt aqueous solution is 10-25 mg / mL.
4. The preparation method according to claim 2, characterized in that: The 2-hydroxy-5-fluoropyrimidine and zinc salt contain Zn 2+ The molar ratio is (2.8-3.2):1; the mass ratio of LL37 and 2-hydroxy-5-fluoropyrimidine is (0.2-2):(5-8).
5. The preparation method according to claim 2, characterized in that: The zinc salt is selected from one or more of zinc nitrate, zinc chloride, zinc sulfate, zinc acetate or zinc gluconate.
6. The preparation method according to claim 2, characterized in that: The standing reaction time is 20 to 60 minutes, and the standing reaction temperature is 10 to 40°C.
7. A pharmaceutical composition, characterized in that The invention comprises the LL37@ZPF-2 complex according to claim 1 or the LL37@ZPF-2 complex prepared by the preparation method according to any one of claims 2 to 6 and a poloxamer 407 gel solution.
8. The pharmaceutical composition according to claim 1, characterized in that In the poloxamer 407 gel solution, the concentration of poloxamer 407 is 15-18wt%, and the solvent of the poloxamer 407 gel solution is selected from any one of citrate buffer, phosphate buffer or water; the dosage ratio of the LL37@ZPF-2 complex and the poloxamer 407 gel solution is (0.5-3.5) mg:1 mL.
9. The pharmaceutical composition according to claim 8, characterized in that The administration route of the pharmaceutical composition is spray administration.
10. Use of the LL37@ZPF-2 complex according to claim 1, or the LL37@ZPF-2 complex prepared by the preparation method according to any one of claims 2 to 6, or the pharmaceutical composition according to any one of claims 7 to 9 in the preparation of a drug for promoting wound healing.